Coping With Internal Politics in Organizations: None (International Journal of Scientific Research and Management (IJSRM), 2019)
Every organization has its own unique share of internal politics. A utopian non-political organization is non-existent. When organizations are faced with fierce internal politics, it is a natural tendency for the affected individual(s) and group(s) to fight back or take flight. Internal politics can emerge from individual and (or) group interests. Again, internal politics can either have negative or positive effects on organizations depending on whether they enhance or stultify individuals and organizational objectives. Individual goals motivate one to move up the organization’s ladder, while organizational objectives guide entities toward the intended end. Therefore, internal politics which enhance individual and (or) organizational objectives should be promoted whilst those which curtail the same, need to be discouraged. Those in leadership in organizations need to strive to ensure that internal politics only propel the best of the best to leadership positions. Notwithstanding, playing the right internal politics card meticulously could therefore be a competitive hedge for those who want an extra-hidden push to where they want to be in organizations. Organizational objectives, however, must always act as the plumb-line to measure authenticity of internal politics in organizations. Hence, authentic internal politics in organizations should indiscriminately offer the necessary support to individuals and (or) groups to actively enhance their objectives.